Pelatihan Manajemen Usaha Petani Kentang di Desa Cintanagara Kecamatan Cigedug Kabupaten Garut - Tintin Febrianti; Rama Adi Pratama (Universitas Muhammadiyah Parepare)
One of the weaknesses of farmers in Indonesia is related to the problem of managing their farming business. Farmers usually carry out their business activities as part of the way of life so that the management processes are not passed as they should, both from the planning, organizing, implementing and controlling stages of the business. Likewise with farmers in the Tonggoh Factory Village, Cintanagara Village, Cigedug District, Garut Regency. With this background, this community service is carried out. Using the training method, changes in both the knowledge and management skills of the trainees can be measured. After participating in training activities, partner knowledge increases with an understanding of the management function (POAC). Necessary formation of Women Farmers Group as a supporter of management and play a role in the diversification of processed potato products.